Subjecting Dams to Early Life Stress and Perinatal Fluoxetine Treatment Differentially Alters Social Behavior in Young and Adult Rat Offspring - Houwing, Danielle J.; Staal, Laura; Swart, Judith M.; Ramsteijn, Anouschka S.; Wöhr, Markus; de Boer, Sietse F.; Olivier, Jocelien D. A. (Frontiers in Neuroscience, 2019)
Recently, the putative association between selective serotonin re-uptake inhibitor (SSRI) exposure during pregnancy and the development of social disorders in children has gained increased attention. However, clinical studies struggle with the confounding effects of maternal depression typically co-occurring with antidepressant treatment. Furthermore, preclinical studies using an animal model of maternal depression to study effects of perinatal SSRI exposure on offspring social behavior are limited. Therefore, the aim of this study was to investigate effects of perinatal fluoxetine exposure on juvenile and adult social behavior in male and female rat offspring, using an animal model of maternal vulnerability. We exposed heterozygous serotonin transporter (SERT) deficient female rats to early life maternal separation stress, and used this as a model for maternal vulnerability. Control and early life stressed heterozygous serotonin transporter knockout (SERT) dams were treated with the SSRI fluoxetine or vehicle throughout gestation and lactation. Subsequently, both male and female wildtype (SERT+/+) and heterozygous (SERT+/-) rat offspring were tested for pup ultrasonic vocalizations (USVs), juvenile social play behavior and adult social interaction.Fluoxetine treatment of the dams resulted in a reduced total USV duration in pups at postnatal day 6, especially in SERT+/+ males. Perinatal fluoxetine exposure lowered social play behavior in male offspring from both control and early life stressed dams. However, in females a fluoxetine-induced reduction in juvenile play behavior was only present in offspring from control dams. Offspring genotype did not affect juvenile play behavior. Despite fluoxetine-induced behavioral effects at juvenile age, fluoxetine reduced male adult social behavior in offspring from control dams only. Effects of fluoxetine on female adult social behavior were virtually absent. Interestingly, early life stress in dams increased adult social exploration in vehicle exposed SERT+/+ female offspring and total social behavior in fluoxetine exposed adult SERT+/- male offspring. Furthermore, SERT+/- males appeared less social during adulthood compared to SERT+/+ males. Overall, the present study shows that chronic blockade of the serotonin transporter by fluoxetine during early development has a considerable impact on pup USVs, juvenile social play behavior in both male and female offspring, and to a lesser extent on male social interaction in adulthood.